Способи тлумачення нормативно-правових договорів - Черновол, С. О.; Chernovol, S. O. (Науковий вісник Академії муніципального управління. Серія: Право. – 2015. – Вип. 1, Ч. 1. – С. 56-62, 2015)
Стаття присвячена питанню тлумачення нормативно-правового договору, розкриттю теоретичних та практичних питань нормативного договору як джерела і форми права, його місця і ролі у врегулюванні суспільних відносин, розкриттю його сутності та змісту. Розглянуто проблеми розвитку нормативного договору у вітчизняній правовій системі, застосування договірного регулювання суспільних відносин, процедура договірної правотворчості.

The article is devoted to the interpretation of the regulatory agreement , the disclosure of theoretical and practical issues of normative treaties as the source and form of law, its place and role in the regulation of public relations , disclosure of its essence and content. The problems of development of normative agreement in Ukrainian legal system , the use of contractual regulation of social relations , the process of lawmaking treaty . The work carried out theoretical generalization and solving scientific problems, was to identify the specifics of the legal technique of creation and interpretation of regulatory agreements and some of its species in order to improve lawmaking, pravointerpretatsionnoy and practice. The technique of creating a regulatory agreement proposed to be defined as a technique of drawing up the draft text of the agreement and the procedures for its conclusion and entry into force. General requirements for the art of creating the regulatory agreement proposed to be divided into textual and procedural. Separately allocated a group of requirements for the use of special means of legal technique when creating the regulatory text of the treaty. The peculiarities of the legal technique of creating international, constitutional law, administrative regulations and collective agreements. Revealed the structure of the legal interpretation of the art regulatory agreements. It is proved that this structure can be distinguished instrumental (means of interpretation) and technological part. The instrumental part is represented by means of interpretation, which, depending on the degree of the need to allocate suggested: the basic needs required additional and optional. Shows the general characteristics of these types of means of interpretation. The peculiarities of the legal interpretation of certain types of machinery regulatory agreements.

Статья посвящена вопросам толкования нормативно-правового договора, раскрытию теоретических и практических вопросов нормативного договора как источника и формы права, его места и роли в регулировании общественных отношений, раскрытию его сути и содержания. Рассмотрены проблемы развития нормативного договора в отечественной правовой системе, применения договорного регулирования общественных отношений, процедура договорного правотворчества.
Способы толкования нормативно-правового договора
Methods of interpretation regulatory agreement
Черновол С.О. Способи тлумачення нормативно-правових договорів / Черновол С.О. // Науковий вісник Академії муніципального управління. Серія: Право. – 2015. – Вип. 1, Ч. 1. – С. 56-62.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; договір; нормативно-правовий договір; тлумачення договору; договор; нормативно-правовой договор; толкование договора; contract; legal agreement; interpretation of the contract